Proceedings of the 1st Progress in Social Science, Humanities and Education Research Symposium (PSSHERS 2019) 2020
DOI: 10.2991/assehr.k.200824.199
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Jogging on the Improvement of Physical Fitness

Abstract: The aim of this study was to determine the effect of jogging to enhance the physical fitness of students in Sport Science Department, Universitas Negeri Padang. Quasi-experiment study was used in this research. The sample of this research was 20 students taken through purposive sampling technique. Data were taken with an instrument of Rockport run 1600 meters, and analyzed with comparative test (t-test) and significant level of 5%. results of the study: the level of students' physical fitness before treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…The dominant sport chosen by Gresik Government employees during the Covid-19 pandemic was Jogging. One of the benefits of jogging is that it can improve physical fitness [13]. In addition, Nabsakom et al (2006) suggested that jogging effectively improves depression, stress, and fitness [14].…”
Section: Figure 7 Frequency Of Exercisementioning
confidence: 99%
“…The dominant sport chosen by Gresik Government employees during the Covid-19 pandemic was Jogging. One of the benefits of jogging is that it can improve physical fitness [13]. In addition, Nabsakom et al (2006) suggested that jogging effectively improves depression, stress, and fitness [14].…”
Section: Figure 7 Frequency Of Exercisementioning
confidence: 99%